The internet of people, things and services workplace transformations - Simmers, Claire 1950-; Anandarajan, Murugan 1961- (Routledge studies in employment relations, 2018)
The transformational technologies of the Internet-Web compound continue to exert a vast and readily apparent influence on the way we live and work. In recent times, internet penetration is now very high in most parts of the world, impacting the context and content of the workplace and the boundary between work and private life is even more porous. Not only has the reach increased, but the technologies to access the Internet-Web have further evolved towards increasing portability. The hardware evolution from desktops to laptops to mobile technologies (phones, tablets, watches, eyeglasses) marches forward. The increasing mobility and 24/7 accessibility offers the opportune time to revisit the transformations occurring. Today the Internet consists of billions of digital devices, people, services and other physical objects with the potential to seamlessly connect, interact and exchange information about themselves and their environment. Organizations now use these digital devices and physical objects to produce and consume Internet-based services. This new Internet ecosystem is commonly referred to as the Internet of People, Things and Services (IoPTS). In this follow-up to their 2006 volume, Simmers & Anandarajan examine how The Internet of People, Things and Services (IoPTS) transforms our workplaces. Information and communications technology (ICT) expansion from desktops to laptops to ubiquitous smart objects that sense and communicate directly over the internet - the IoPTS - offers us the opportune time to revisit how the Internet transforms our workplaces